The Iconography of the Virgin of Mercy and of the Virgin of Arrows in the Art of Bologna and Romagna in the 14th and 15th Centuries - Castaldi, Tommaso (Eikón / Imago, 2015)
The oldest examples of the subject of the Virgin of Mercy have always been localized by scholars in central Italy, between Florence and Siena: thanks to Franciscans and Dominicans and to lay confraternities, which can be identified as the main patrons, the subject quickly spreads in the painting of banners and devotional altarpieces. This essay aims not only to summarize the origins of this iconography and its manifold symbolisms, but above all, despite current studies, it wishes to highlight the importance of Romagna in the diffusion of the theme, as demonstrated by the antiquity and the multitude of survived examples in this area. An original variation of the subject, which is present also in Emilia-Romagna and which this paper tries to examine in depth, is called the Virgin of arrows: here the mantle becomes an invincible shield protecting humanity from the punishment of God, shaped through the arrows which break against its surface.